Peningkatan Kompetensi Guru Bahasa Inggris dalam Penulisan Artikel pada Open Journal System (OJS) - Muhaiminah Akib; Dian Saputra; Ahmad Wael; Ruslan Hasyim (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Teacher training activities in writing article and publication on the Open Journal System are strategic to be carried out. This is expected to have an impact on increasing the ability of teachers in writing scientific papers and also publications. In addition, it is hoped that through the writing culture, an academic climate will be developed among teachers. The implementation of training articles and publications in journals for Musyawarah Guru Mata Pelajaran (MGMP) Bahasa Inggris Sekolah Menengah Atas (SMA) Kota Sorong group is expected to be a solution to the lack of teacher publications. In addition, participants who will take part in this training will share the knowledge gained with their fellow teachers at their home school. The results of this Community Service activity show an increase in the ability of teachers from the average pre-test score of 59 and post-test 89. The conclusion from this activity is that the training carried out has succeeded in increasing the competence of English teachers in Article Writing and Publication in the Open Journal System (OJS).